Carbon deposition from biotar by fast pyrolysis using the chemical vInfiltration process within porous low-grade iron ore for iron-making - Rozhan, Alya Naili; Cahyono, Rochim B.; Yasuda, Naoto; Nomura, Takahiro; Hosokai, Sou; Purwanto, Hadi; Akiyama, Tomohiro (American Chemical Society (ACS Publications), 2012)
This paper presents a technology for iron-making using biomass and a low grade iron ore by implementing chemical vapor infiltration (CVI) for the tar carbonization process. In this process, tar vapor from pyrolysis of biomass was infiltrated within a porous ore and carbon deposition occurred on the pore surface. For preparation, ore sample was heated in an electric furnace to decompose combined water in the sample, creating nanosized pores. In the experiments, the traditional slow pyrolysis was compared with fast pyrolysis to determine which condition is better for maximizing carbon deposition. Tar vapor from the pyrolysis process was introduced into the porous ore and trapped inside it, where tar decomposed and carbonized within the pores. The product of this process which is a carbon−magnetite composite with close arrangement of iron ore and carbon is useful for reduction of iron by carbon and is able to lower the temperature needed for reduction of iron to occur, as compared to that in steelworks. The purpose of this research is to compare the effects of slow pyrolysis and fast pyrolysis processes on the amount of carbon deposited within iron ore by the tar carbonization process and to observe the reduction reactivity of the carbon-deposited iron ore.